Analisis Perlakuan Branch Profit Tax atas Bentuk Usaha Tetap Perusahaan Pelayaran Luar Negeri - Andy Famela Silalahi; Yohanes - (Jurnal Akuntansi dan Pajak, 2021)
This study aims to analyze the interpretation of Branch Profit Tax (BPT) according to Directorate General of Taxes (DJP) and permanent establishment (PE) of shipping company, as well as to provide input to settle this differences in interpretation by making confirmation letter or changing the regulation. The PE studied is the Singapore PE because there were differences in interpretation of the Minister of Finance Decree (KMK) number 417/KMK.04/1996 regarding BPT between the PE and DJP. This study uses The Theory of Legal Interpretation and the concept of legal interpretation. The research approach used is qualitative with case study. Data collection techniques used are interviews and documentation. The analysis technique uses descriptive, content, and thematic analysis techniques. The results show that BUT X used a systematic or logical interpretation and interpreted the income tax rate of 2.64% in KMK number 417/KMK.04/1996 includes BPT, while DGP used grammatical interpretation and interpreted the income tax rate of 2.64% in the KMK does not include BPT. The input given is to change the KMK number 417/KMK.04/1996 so that there are no differences in interpretation in the future and the KMK can be used for the PE of shipping companies from all partner countries.